2015
DOI: 10.2466/06.pms.121c28x4
|View full text |Cite
|
Sign up to set email alerts
|

Players' Perceptions of Home Advantage in the Australian Rugby League Competition

Abstract: This study was designed to pilot a survey to explore players' perception of home advantage in a rugby league. Twenty-seven players from one team with an identified home advantage believed a home advantage existed as a result of their home crowd (52%), family and friends' support (41%), normal travel (45%) and sleeping arrangements (37%), home weather conditions (48%), and familiarity with playing amenities (37%). However, the players were less definite about influences while playing away from home. The current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Previous work has shown that situational and contextual factors such as match location and environmental conditions could either positively or negatively impact on a team's perceptual, 19 technical and physical performance output. 20 Thus, future work may wish to consider such factors when investigating the performance indicator characteristics of higher and lower performing NRL teams.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that situational and contextual factors such as match location and environmental conditions could either positively or negatively impact on a team's perceptual, 19 technical and physical performance output. 20 Thus, future work may wish to consider such factors when investigating the performance indicator characteristics of higher and lower performing NRL teams.…”
Section: Resultsmentioning
confidence: 99%
“…Home advantage has previously been shown to exist (Goumas 2014;Lo et al 2019;Fullagar et al 2019). Through surveys with NRL players, McGuckin et al (2015) identified that the home crowd, normal travel/transport and the presence of family/friends were the key factors that players perceived to have a positive influence on performance in home matches. When playing away from home, the same players ranked the different meals and sleeping arrangements as the largest negative influences, which might explain some aspects of the reduction in performance (McGuckin et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have attempted to measure the extent of home advantage within the NRL. McGuckin et al ( 2015 ) for example defined home advantage as teams winning more that 50% of home games. However, there are a number of limitations to this type of definition.…”
Section: Section 2—the Empirics Of Unconscious Bias In Rugby Leaguementioning
confidence: 99%